Adolescent mental health in rural settings: the role of artificial intelligence and community engagement - Grenon, Sarah; Hoang, Khanh N.; Luo, Si; Koch, Amie (Frontiers in Public Health, 2025)
Adolescents in rural communities face persistent mental health disparities due to provider shortages, social isolation, and stigma. Traditional care models remain insufficient. This perspective explores how artificial intelligence (AI) tools combined with community engagement strategies can enhance adolescent mental health support in underserved settings. A targeted literature review identified best practices and innovative models that integrate AI in culturally relevant ways. Findings highlight the importance of trusted community partnerships and digital literacy, particularly prompt literacy, in ensuring safe and effective AI use. Nurses are uniquely positioned to lead these efforts, promoting health equity and digital inclusion through community-based, AI-enabled interventions.